Power electronics applied to industrial systems and transports. - Patin, Nicolas (Lecturer) (ISTE Press, Ltd. ; Elsevier, 2016)
Through three detailed chapters, this book outlines the functions and capabilities of static converters such as sensors used ini protection devices and energy storage devices with a thorough review of the technologies and applications of all these components, including monitoring aspects.